2022
DOI: 10.1007/s11571-022-09869-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale entropy of ADHD children during resting state condition

Abstract: This present study aims to investigate neural mechanisms underlying ADHD compared to healthy children through the analysis of the complexity and the variability of the EEG brain signal using multiscale entropy (MSE), EEG signal standard deviation (SDs), as well as the mean, standard deviation (SDp) and coefficient of variation (CV) of absolute spectral power (PSD). For this purpose, a sample of children diagnosed with attention-deficit/hyperactivity disorder (ADHD) between 6 and 17 years old were selected base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Sokunbi et al (2013) reported significant reductions of SampEn in adults with ADHD relative to the controls in the superior frontal and anterior cingulate gyrus which was replicated for pre-adolescents with ADHD in the current study (Figure 1(C)). Our results aligned with existing literature in resting-state using other neuroimaging modalities such as EEG and MEG in which complexity was found lower in the participants with ADHD than in the healthy controls (Angulo-Ruiz, Muñoz, Rodríguez-Martínez, Cabello-Navarro, & Gómez, 2022;Fernández et al, 2009;Gu, Liu, & Woltering, 2022;Gómez et al, 2013;Hu et al, 2021;Rezaeezadeh, Shamekhi, & Shamsi, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Sokunbi et al (2013) reported significant reductions of SampEn in adults with ADHD relative to the controls in the superior frontal and anterior cingulate gyrus which was replicated for pre-adolescents with ADHD in the current study (Figure 1(C)). Our results aligned with existing literature in resting-state using other neuroimaging modalities such as EEG and MEG in which complexity was found lower in the participants with ADHD than in the healthy controls (Angulo-Ruiz, Muñoz, Rodríguez-Martínez, Cabello-Navarro, & Gómez, 2022;Fernández et al, 2009;Gu, Liu, & Woltering, 2022;Gómez et al, 2013;Hu et al, 2021;Rezaeezadeh, Shamekhi, & Shamsi, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Canonical PSD EEG studies differ in their trend during maturation depending on the power analysis performed (absolute PSD or relative PSD). As several authors have argued, absolute PSD (Gasser et al, 1988;Miskovic et al, 2015;Rodríguez-Martínez et al, 2012Segalowitz et al, 2010) decreases with age, while the variability increases (Angulo-Ruiz et al, 2021, 2022, which has been attributed to the natural maturation processes of the nervous system, such as neural pruning (Whitford et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Canonical PSD EEG studies differ in their trend during maturation depending on the power analysis performed (absolute PSD or relative PSD). As several authors have argued, absolute PSD (Gasser et al, 1988; Miskovic et al, 2015; Rodríguez-Martínez et al, 2012, 2017; Segalowitz et al, 2010) decreases with age, while the variability increases (Angulo-Ruiz et al, 2021, 2022), which has been attributed to the natural maturation processes of the nervous system, such as neural pruning (Whitford et al, 2007). In this regard, our results emphasize that the decrease in absolute PSD would be mostly due to a decrease in the AP component with age, as reported in other studies (Cellier et al, 2021; Dave et al, 2018; Donoghue et al, 2020a, 2020b; He et al, 2019; Hill et al, 2022; McSweeney et al, 2021, 2023; Schaworonkow and Voytek, 2021) since it appears at all frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural activity patterns in EEG signals have been more commonly analyzed with complexity and entropy measures [50]- [52]. Multiscale entropy, in particular, has been used to discriminate between different neurological disorders, and between patients with generalized seizures from those with focal seizures [50].…”
Section: Discussionmentioning
confidence: 99%